A Public Speaking Training Model for Enhancing Senior High School Teachers' Pedagogical Communication Competence - Pauline Tricia Putri Andriani; Pujiriyanto Pujiriyanto (AL-ISHLAH: Jurnal Pendidikan, 2025)
Effective pedagogical communication is essential for high school teachers to create engaging and interactive learning environments. However, many teachers struggle with public speaking, which negatively impacts classroom dynamics and student motivation. This study aims to develop and evaluate a structured public speaking training model to enhance teachers’ communication competencies. Using a Research and Development (RD) approach based on the ADDIE model, the study designed a public speaking training book tailored to senior high school teachers. The model was validated by content and media experts, and its effectiveness was tested through a quasi-experimental pretest–posttest control group design involving 40 teachers in Denpasar, Indonesia. Expert validation yielded high feasibility scores for both content (125) and media (76), indicating the training model was “very suitable.” Field testing showed strong practicality (92% average rating). The experimental group improved significantly in public speaking competence, with a gain score of 0.5 (moderate), compared to 0.2 (low) in the control group. Statistical analysis confirmed these differences as significant (t = -10.466, p 0.001; ANOVA F = 8.609, p 0.05). The training model is feasible, practical, and effective in improving pedagogical communication. It addresses the gap in teacher professional development by focusing on public speaking as a core competency. This model can be integrated into continuing professional development programs to enhance teaching quality in line with Education 5.0 demands.